Qur'anic guidance on the legal status of human embryos - Zawawi, Majdah; Hussin, Nasimah (2012)
The advent of science and technology has allowed for the creation of embryos outside a mother’s womb. This possibility has led to problems among others when there is divorce, who should have ownership over the embryos. If no one has ownership, how these embryos shall be treated? Should they be allowed to perish or could they be donated to other infertile couples, or could they be used for research purposes. These are the problems surrounding the human embryos created outside the womb. This paper aims at considering the legal status of human embryos created outside the womb through analysis of Qur’anic verses. This will help determine the legality of certain acts involving these embryos. The research utilizes the doctrinal analysis of primary and secondary sources. The Qur’an and Sunnah (in light of the legal exegesis and interpretation of the two sources) are analysed to derive the basic principles governing the area. A thorough examination of fiqh literature of the Sunni scholars on the subject matter is carried out and the principle of “tarjih” is used to determine the strongest and practicable opinion. Other related sources are also examined. The evidence is used to compare and verify the findings from the research. The research shows that Islam places high respect towards the human embryo due to its potential to develop into a human being. Thus treatment of the human embryo must be in line with this special position given to human beings based on Qur’anic injunctions.